2011
DOI: 10.1007/s10753-011-9345-1
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers: Exhaled Nitric Oxide and Carbon Monoxide During the Ovarian Cycle

Abstract: Nitric oxide (NO) production and carbon monoxide (CO) production are increased in inflammatory lung diseases. Although there are some pieces of evidence for hormonal modulation by estrogen, little is known about exhaled NO and CO during the ovarian cycle. In 23 subjects, we measured exhaled NO and CO by an online analyzer. Significantly higher levels of exhaled NO were found at the midcycle compared with those in the premenstrual period or during menstruation. Higher levels of CO were after ovulation and reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The gender effect may be due to more heavy smokers in the male group, as heavy smokers tend to have a higher concentration of COHb [3,24,45]. Moreover, some studies showed that females may have lower exhaled CO concentrations during menstruation due to loss of blood, which has a high affinity with CO [46]. The baseline exhaled CO concentration was positively associated with the number of cigarettes smoked daily and weekly, similar to other studies [20,24,26,39,43].…”
Section: Discussionsupporting
confidence: 77%
“…The gender effect may be due to more heavy smokers in the male group, as heavy smokers tend to have a higher concentration of COHb [3,24,45]. Moreover, some studies showed that females may have lower exhaled CO concentrations during menstruation due to loss of blood, which has a high affinity with CO [46]. The baseline exhaled CO concentration was positively associated with the number of cigarettes smoked daily and weekly, similar to other studies [20,24,26,39,43].…”
Section: Discussionsupporting
confidence: 77%
“…Recent studies indicate that eCO values may be slightly impacted by acute hyperventilation [137]. Interestingly, eCO may fluctuate with the ovarian cycle in women [138]. eCO levels increased after ovulation peaked in the premenstrual phase, whereas eNO values peaked at mid-cycle [138].…”
Section: Carbon Monoxide In Exhaled Breathmentioning
confidence: 99%
“…Interestingly, eCO may fluctuate with the ovarian cycle in women [138]. eCO levels increased after ovulation peaked in the premenstrual phase, whereas eNO values peaked at mid-cycle [138]. …”
Section: Carbon Monoxide In Exhaled Breathmentioning
confidence: 99%
“…Due to an increase in erythrocytes' catabolism, reticulocyte counts, and nitric oxide (NO) and progesterone expression and activation of heme oxygenase 1 (HO-1), particularly in the myometrial, vascular endothelial and smooth muscle cells, the production of endogenous carbon monoxide (CO) is elevated during the luteal phase of the menstrual cycle, providing protection against the endothelial oxidative stress. NO levels augment in the midcycle (74).…”
Section: Inflammatory Responses During Menstruationmentioning
confidence: 95%